SOURCES OF MALAYSIA’S INCOME AND ITS ALLOCATIONS IN CONTEXT ISLAM'S PUBLIC FINANCIAL IN NEWEST ERA - oktarina, amimah; Desiana, Rina (Institut Agama Islam Bengkulu, 2019)
In order to build an Islamic economic system in Islamic state, a state should manage its finance based on the principles of Sharia, both in the terms of earning or incomes and their allocations on the earnings side, a state should manage their incomes according to Islamic way. Than the result of their incomes should be allocated in order to achieve their goals, which is the prosperity of society. Tax is a policy which is settled by a government and decided according to the needs or necessities of state its self. For example, Malaysia has decided and managed their incomes sources such as tax, zakat, and awqaf. And they were allocated according to the needs or necessities of a state such as infrastructure, salaries, subsidies, and also to eight parts of zakat receiver.